Mapeamento e abordagens legais das redes de bioprospecção no Brasil - Marques, Lana Grasiela Alves (2014)
This work has as its objective to map the bioprospection networks in Brazil, as well as the legal approaches involved in the access to genetic resources for bioprospection purposes. Bioprospection has become one of the main topics of discussion in recent years, since the Biological Diversity Convention (CBD in Portuguese) recognized the sovereignty of each country over genetic resources found within their territories. Moreover, the CDB recognized the right of each signatory country in the implementation of their own national biodiversity policies. In order to fulfil these and other demands, Brazil has established actions focused on the conservation and sustainable use of biodiversity through research programmes and networks. In this context, this work has identified the progress regarding the creation and strengthening of research networks in biodiversity, as well as the results obtained through the development of products, especially bio-pharmaceuticals. However, the Provisional Policy No. 2.186-16/2001, considered to be the regulatory framework regarding the genetic resources in Brazil, has established norms that have caused obstructions to the development of bioprospective research. As a result, there is a common agreement about the need to improve the Provisional Policy No. 2.186-16/2001, which is presently in course through a Law Bill. In face of these facts, it is hoped that the networks and programmes in bioprospection can transform the natural resources in economic gain, leverage the scientific and technological development and add value to the goods and services derived from these natural resources.